(untitled) (Research, Society and Development, 2021)
The construction of an Urban Environmental Quality Index (UQI) is a complex task, which varies and combines continuously over the urban landscape in several scales of analysis. The objective was to make a comparison between urban centers on environmental quality, besides verifying the environmental perception of the community regarding the quality of urban life and, finally, to propose two mitigating measures for each indicator adopted. The research was carried out in the city of Marabá, in the cores Cidade Nova (Novo Horizonte) and Nova Marabá (Folha 22). For the primary data, 208 simple forms were applied, composed of objective questions and the adoption of scores from 0 to 10 for each environmental indicator that composed the IQAU. As for the secondary data, a survey of documentary data was carried out to add knowledge about the indicators used in the research, as well as the correlation regarding the quality of urban life, to identify whether such indicators are relevant to assess the quality of the environments chosen in the research, for this, a time frame between the years 2009 to 2018 was used. The data obtained and analyzed indicate that the Nova Marabá core (IQAU = 47.96) obtained a "bad" classification. The core Cidade Nova (IQAU = 63.17), this (+15.21), which proved the influence that an urban planning has on environmental quality was identified as "intermediate". The determining factor for the classifications based on the quantifications, was the urban planning adopted in Cidade Nova, which was not identified in the NB. With this, it was verified that urban planning in cores of the municipalities can improve the IQAU, and the health of the municipalities’ residents.